Analisis Hubungan antara Nilai Mata Kuliah Metode Statistika dan Mata Kuliah Teori Peluang pada Mahasiswa Statistika dengan Korelasi Somers' D - Reski Wahyu Yanti; Retno Mayapada; Andi Sri Rahayu Kasma; Syandriana Syarifuddin; Andi Seppewali (Program Studi Matematika Universitas Sulawesi Barat, 2023)
The subjects studied at university are often interrelated and form an intact of complete knowledge. This study aims to analyze the asymmetrical relationship between Statistical Methods scores and Probability Theory scores in Statistics students through Somers' d correlation analysis. Based on the analysis performed, it was found that there was a strong correlation (0.612 and 0.716) between the scores obtained by students in the Statistical Methods and Probability Theory. The analysis also shows that the scores of the Statistical Method that students obtained has a significant influence on students' Probability Theory scores. So it can be concluded, that the higher the student's Statistical Method score obtained in the early semester, the higher the chance for students to get high Probability Theory scores in the following semester.